Information Resources, Services and Information Needs in Food Sciences and Technology in India: A Survey - Sangameswaran, S. V.; Gopinath, M. V.; Amla, B. L. (Journal of Information and Knowledge, 1976)
It has been proposed to develop the CFTRI Library into a Sectoral Information Centre within the frame-work of the National Information System for Science and Technology (NISSAT) proposed to be established during the Fifth Plan period. A draft plan for this system " Food Science and Technology Information Service" (FOSTIS) has been prepared. One of the recommendations of this plan is to conduct a survey of information resources and requirements in the country in the field of food science and technology. Accordingly, a survey was conducted to solicit information from potential users on the basis of a questionnaire specially designed for the purpose. The returns have been analysed and the results are presented in this paper. The survey clearly indicates the need for establishing FOSTIS at CFTRI. The most encouraging point of this survey is the willingness of a majority of the organisations to become members of FOSTIS by subscribing to its services. The findings of the survey will be useful in tailoring the services of FOSTIS to suit the requirements of the users.